2021
DOI: 10.3390/jcm10184175
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Guidelines for PTSD: A Systematic Review

Abstract: Background: The aim of this review was to assess the quality of international treatment guidelines for post-traumatic stress disorder (PTSD), and identify differences between guideline recommendations, with a focus on the treatment of nightmares. Methods: Guidelines were identified through electronic searches of MEDLINE, CINAHL, PubMed, Embase and Science Direct, as well as web-based searches of international guideline repositories, websites of psychiatric organisations and targeted web-searches for guidelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 42 publications
(57 reference statements)
2
67
0
1
Order By: Relevance
“…However, specific therapeutic approaches to manage post-traumatic stress disorder might be needed. 36 With obesity being associated with both non-recovery and severity of long COVID, whether weight reduction using combined pharmacological and non-pharmacological approaches can ameliorate long COVID warrants further investigation. Beyond diet and lifestyle interventions, GLP-1 analogues have been reported to achieve clinically important weight reduction in adults.…”
Section: Discussionmentioning
confidence: 99%
“…However, specific therapeutic approaches to manage post-traumatic stress disorder might be needed. 36 With obesity being associated with both non-recovery and severity of long COVID, whether weight reduction using combined pharmacological and non-pharmacological approaches can ameliorate long COVID warrants further investigation. Beyond diet and lifestyle interventions, GLP-1 analogues have been reported to achieve clinically important weight reduction in adults.…”
Section: Discussionmentioning
confidence: 99%
“…For pharmacotherapy, selective serotonin reuptake inhibitors (SSRIs) are generally regarded as the first-line therapy, specifically for fluoxetine or paroxetine. The serotonin/norepinephrine reuptake inhibitor venlafaxine is also seen as a common recommendation for first-line pharmacotherapy [ 6 ]. A systematic review conducted by Martin et al in 2021 found that one-third of guidelines recommended psychotherapy over pharmacotherapy, and all chose cognitive-behavioral therapy (CBT) as first-line [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The serotonin/norepinephrine reuptake inhibitor venlafaxine is also seen as a common recommendation for first-line pharmacotherapy [ 6 ]. A systematic review conducted by Martin et al in 2021 found that one-third of guidelines recommended psychotherapy over pharmacotherapy, and all chose cognitive-behavioral therapy (CBT) as first-line [ 6 ]. Our patient was maintained on fluoxetine while inpatient and recommended for trauma-focused CBT outpatient as part of her therapy per these guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…There are no published RCTs that examined the direct effect of THC or CBD on depressive symptoms [ 155 ]. However, many published RCTs have examined the effects of THC or THC:CBD on other conditions, such as pain and multiple sclerosis (MS) [ 156 ].…”
Section: The Ecs In Human Studies Of Depressionmentioning
confidence: 99%